TRAINING ON ANIMAL FEED PROCESSING AND TREATMENT OF REPRODUCTIVE DISORDERS IN PALM INTEGRATED CATTLE FARMING AREA IN WEST KALIMANTAN - Hidayatik, Nanik; Lamid, Mirni; Hermadi, Herry Agoes; Warsito, Sunaryo Hadi; Suprayogi, Tri Wahyu; Safitri, Erma; Pratomo, Andrika Indra (Universitas Airlangga, 2024)
West Kalimantan Province is one of the provinces that has a large area of oil palm plantations which can become integrated cattle farms. Oil palm plantations provide a source of feed that comes from palm oil processing waste and green grass around the oil palm trees. However, this waste contained not sufficient nutrients if given directly, so needed feed processing to increase the nutrition. The community service team from the Faculty of Veterinary Medicine, Universitas Airlangga carried out activities to increase the knowledge and skills of farmers in processing palm oil waste feed and carried out reproductive examination activities on female cattle. The output target to be achieved is increasing the ability of farmers to make feed from palm oil waste that can sufficient for livestock nutritional needs and increased of reproductive health of cows. This activity held on 20 – 23 July 2023 in Tonang Village, District. Sengah Temila, Kab. Landak, West Kalimantan. The activity was attended by 40 participants consisting of breeders, medical officers and veterinarians from the Dinas Ketahanan Pangan, Pertanian dan Perikanan Kabupaten Landak dan Dinas Perkebunan dan Peternakan Provinsi Kalimantan Barat. The first day's activities were carried out by delivering outreach and training materials on processing palm oil waste feed through silage and fermentation methods, making UMB and UMMB, and carrying out reproductive examinations and treatment of female cattle. The outcomes that have been achieved include increasing farmers' understanding and skills regarding how to make silage and palm frond fermentation, as well as UMB and UMMB as additional feed. Health and reproductive disorders examination of female cattle were carried out on 2 female cattle belonging to the Koperasi Produsen Landak Mandiri and 17 female cattle belonging to the Alam Raya Hijau Group. Based on the examination, data was obtained that 7 cows were pregnant, 1 cow had endometritis, and 11 cows were declared to be in normal reproductive condition. The conclusion that can be drawn from this activity is that the participants' knowledge about the given topic increases and the reproductive health of female cattle can be handled with appropriate examination and treatment.